Norway : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2001 Article IV Consultation highlights that the real mainland (non-oil) GDP of Norway is estimated to have grown well below potential in 2001, at 1u percent. Although high oil prices supported household confidence and domestic activity through most of the year, the global slowdown has recently begun to affect Norway. Labor market conditions remain tight in service sectors, but weakened in technology and traditional export industries. Despite high domestic cost increases, consumer price inflation has been held in check by low krone import prices.